Frequency and diversity of the cases reported at Oncology care clinic of Holy Family Hospital Rawalpindi during August 2022: Frequency and Diversity of the Cases Reported at Oncology Care Clinic - Shahid, Rizwana; Khan, Sadia; Aziz, Qaiser; Umar , Muhammad (Pakistan Journal of Health Sciences, 2022)
Although cancers are primarily attributed to genetic mutations, but environmental factors one way or the other are also responsible for influencing the growth of cancerous cells. Objectives: To determine the frequency and diversity of the cases reported at Oncology care clinic of Holy Family Hospital. Methods: A cross-sectional descriptive study was done to ascertain the frequency and diversity of cases that were reported to Oncology care clinic of Holy Family Hospital (HFH) Rawalpindi during August 2022. The data were collected by reviewing the hospital records of the patients. Data was analysed by SPSS version 25.0 and Microsoft Excel 2010. Percentage and frequency of all variables were computed. Statistical difference in mean age of male and females was determined by independent sample t-test. P < 0.05 was considered significant. Results: Mean age of the total 23 cases reporting to Oncology clinic of HFH during August 2022 was 49.91 ± 15.12 years. There were 14(61%) females and 9(39%) males. The gender-based difference in mean age was statistically insignificant (P > 0.13) with 95% CI (-3.20 – 22.80). About 12 and 11 were confirmed and suspected cases respectively. The highest number of cases was first reported in Gynaecology & Obstetrics Unit-I, followed by medical units of HFH. Around 7(30.4%) patients were residents of twin cities (Rawalpindi & Islamabad). Conclusions: Middle aged females are comparatively more in need of screening for early diagnosis and treatment of certain benign and malignant illnesses than those of males